Potentially inappropriate medication in elderly patients in Santiago de Cuba - Irma L. Ortega López; Ivette Reyes Hernández; Niurka M. Dupotey Varela; Danneris Lores Delgado; Yoenia Veranes Vera; Lilisbeth Pupo Benítez; Erenis Guerra Prado (Journal of Pharmacy & Pharmacognosy Research, 2019)
Context: Several studies have reported the high use of inappropriate medication in the elderly, as well as the associated risks; for this reason, it has become a major health problem.